Correction: Publisher Correction: Simultaneous overactivation of Wnt/β-catenin and TGFβ signalling by miR-128-3p confers chemoresistance-associated metastasis in NSCLC - Junchao Cai (Nature Portfolio, 2018)
Nature Communications 8: Article number: 15870 (2017); Published online 19 June 2017; Updated 30 March 2018 In the original version of this Article, the affiliation details for Yan Huang and Li Zhang were incorrectly given as ‘Department of Medical Oncology, Sun Yat-Sen University Cancer Center, Guangzhou 510060, China’, and should have been ‘State Key Laboratory of Oncology in South China, Department of Medical Oncology, Sun Yat-Sen University Cancer Center, Guangzhou 510060, China’.